Childbirth and prolapse: long‐term associations with the symptoms and objective measurement of pelvic organ prolapse. (27th November 2012) - Glazener, C; Elders, A; MacArthur, C; Lancashire, RJ; Herbison, P; Hagen, S; Dean, N; Bain, C; Toozs‐Hobson, P; Richardson, K; McDonald, A; McPherson, G; et al.
Abstract : Objectives: To investigate prolapse symptoms and objectively measured pelvic organ prolapse, 12 years after childbirth, and association with delivery mode history. Design: Twelve‐year longitudinal study. Setting: Maternity units in Aberdeen, Birmingham and Dunedin. Population: Women dwelling in the community. Methods: Data from women were collected 12 years after an index birth and women were invited for examination. Logistic regression investigated associations between risk factors and prolapse symptoms and signs. Main outcome measures: Prolapse symptom score (POP‐SS); objectively measured prolapse (POP‐Q). Results: Of 7725 continuing women, 3763 (49%) returned questionnaires at 12 years. The median POP‐SS score was 2 (IQR 0–4). One or more forceps deliveries (OR 1.20, 95% CI 1.04–1.38) and a body mass index (BMI) over 25 were associated with higher (worse) POP‐SS scores, but age over 25 years at first delivery was associated with lower (better) scores. There was no protective effect if all deliveries were by caesarean section (OR 0.84, 95% CI 0.69–1.02). Objective prolapse was found in 182/762 (24%) women. Women aged over 30 years when having their first baby and parity were significantly associated with prolapse. Compared with women whose births were all spontaneous vaginal deliveries, women who had all births by caesarean section were the least likely to have prolapse (OR 0.11, 95% CI 0.03–0.38), and there was a reduced risk after forceps or a mixture of spontaneous vaginal delivery and caesarean section. Conclusions: These findings are at odds with each other, suggesting that prolapse symptoms and objective prolapse may not be in concordance, or are associated with different antecedent factors. Further follow‐up is planned.